Astrocytic Regulation of Glutamate Transmission in Schizophrenia - Mei, Yu-Ying; Wu, Dong Chuan; Zhou, Ning (Frontiers in Psychiatry, 2018)
According to the glutamate hypothesis of schizophrenia, the abnormality of glutamate transmission induced by hypofunction of NMDA receptors (NMDARs) is causally associated with the positive and negative symptoms of schizophrenia. However, the underlying mechanisms responsible for the changes in glutamate transmission in schizophrenia are not fully understood. Astrocytes, the major regulatory glia in the brain, modulate not only glutamate metabolism but also glutamate transmission. Here we review the recent progress in understanding the role of astrocytes in schizophrenia. We focus on the astrocytic mechanisms of (i) glutamate synthesis via the glutamate-glutamine cycle, (ii) glutamate clearance by excitatory amino acid transporters (EAATs), (iii) D-serine release to activate NMDARs, and (iv) glutamatergic target engagement biomarkers. Abnormality in these processes is highly correlated with schizophrenia phenotypes. These findings will shed light upon further investigation of pathogenesis as well as improvement of biomarkers and therapies for schizophrenia.